Hypothyroidism: clinical presentation, diagnosis, treatment - Wojtachnio, Dominika; Osiejewska, Aleksandra; Bartoszewicz, Jakub; Grądzik, Anna; Nowakowska, Izabela; Kudan, Małgorzata; Gorajek, Anna; Mikut, Karolina (Journal of Education, Health and Sport, 2022)
Introduction and purpose: Hypothyroidism is a common disorder of the endocrine system in which the thyroid gland is not able to produce enough of certain thyroid hormones. Brief description of the state of knowledge: The prevalence of hypothyroidism is between 1 and 6% and it is more common in women and older adults. Untreated significantly decreases the quality of life and increases mortality. Symptoms of hypothyroidism are nonspecific and may be confused with signs of other clinical conditions. The most common symptoms are chronic tiredness and fatigue, weight gain, cold intolerance, dry skin and hair loss. Serum thyroid-stimulating hormone (TSH) is the primary screening test for thyroid disfunction. Standard treatment for hypothyroidism consists of thyroid hormone replacement called levothyroxine. Conclusion: This article reviews basic informations, clinical presentation, diagnosis and treatment of hypothyroidism.